Evaluating The Implementation Of MSME Tax Policies In Indonesia: Benefits, Challenges, And Macroeconomic Implications - Rahmat Burhamzah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing 61.07% to GDP and absorbing 97% of the national workforce. This study aims to analyse the implementation of MSME tax policies in Indonesia, specifically Government Regulation Number 55 of 2022, and to identify their benefits, challenges, and implications for the national economy. The research method uses a qualitative approach with a desk study through secondary data analysis from academic literature, tax regulations, and official government data. The results show that the implementation of the 0.5% Final Income Tax rate facilitates administration and encourages the formalization of MSMEs, but faces challenges such as low tax literacy, limited digital access, and issues of fiscal justice. The study concludes that MSME tax policies have a positive impact on economic inclusion and increased tax compliance, but require improvement through intensive education, administrative simplification, and periodic evaluation to achieve a balance between ease and fairness of taxation